2022
DOI: 10.1183/23120541.00179-2022
|View full text |Cite
|
Sign up to set email alerts
|

The polyhedric reality of the interaction between COVID-19, asthma and inhaled corticosteroids

Abstract: In December 2019, a pneumonia outbreak of unknown origin was identified in Wuhan, China. It was given the label coronavirus disease 2019 (COVID-19) and the virus causing it was named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1, 2]. On 11 March 2020, the World Health Organization (WHO) declared the COVID-19 outbreak a pandemic [3]. By 5 April 2022, there had been 490 853 129 confirmed cases of COVID-19, including 6 155 344 deaths, reported to the WHO [4]. As of 4 April 2022, a total of 11 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In contrast, other studies have provided evidence that ICS may be associated with an additional risk of adverse COVID-19 outcomes and a prolonged time to viral clearance [63] , [64] , [65] . However, ICS in previous studies have not shown a clear or consistent association with COVID-19 outcomes [66] , [67] , [68] . Given the immunomodulatory effects of ICS and the controversial results, Terry et al recently found that ICS use in asthmatics was associated with decreased mortality in COVID-19 [69] .…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, other studies have provided evidence that ICS may be associated with an additional risk of adverse COVID-19 outcomes and a prolonged time to viral clearance [63] , [64] , [65] . However, ICS in previous studies have not shown a clear or consistent association with COVID-19 outcomes [66] , [67] , [68] . Given the immunomodulatory effects of ICS and the controversial results, Terry et al recently found that ICS use in asthmatics was associated with decreased mortality in COVID-19 [69] .…”
Section: Discussionmentioning
confidence: 76%
“…prognosis, including inhibition of pro-inflammatory cytokine and chemokine production and antiviral effects [13,14,48,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mAb and/or high-dose ICS may confer additional risk of poor COVID outcomes in these patients [ 12 , 20 ]. For example, ICS use may increase risk of pneumonia in patients with asthma [ 48 ], reduce ACE-2 expression [ 49 ], or reduce the number of eosinophils in blood [ 50 ], all possible indicators of poor COVID-19 prognosis [ 51 , 52 ]. However, mechanisms have also been suggested by which ICS use may improve COVID-19 prognosis, including inhibition of pro-inflammatory cytokine and chemokine production and antiviral effects [ 13 , 14 , 48 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ICS in asthmatics with COVID-19 diseases has generated conflicting positions among clinicians who supported the possibility of an increased susceptibility towards the development of severe COVID-19 disease and those who argued in favor of their protective role in avoiding SARS-CoV-2 infection or protecting against the risk of severe COVID-19 disease [29 ▪▪ ]. In September 2020, an observational study conducted by Schultze et al [30] highlighted an increased risk of death in asthmatic patients using high dose of ICS, showing a lack of protective role against COVID-19 death in the analyzed studied population.…”
Section: Introductionmentioning
confidence: 99%